Women, fertility, and maternal art in Renaissance Florence - Gislon Dopfel, Costanza, author. Link
1 online resource (x, 297 pages)
Keywords: "Women, Fertility and Maternal Art in Renaissance Florence examines maternity-centered art to reveal women's crucial function in saving Florence from a depopulation catastrophe. Nativity and Madonna and Child images that graced many households and chapels in Florentine society formed a program of visual indoctrination, championing a "birth epic" that glorified the social duty of reproduction but dismissed its high risk. As images emphasizing women's reproductive value multiplied throughout the century, the accounts of their deaths in childbirth and the records of their elaborate public funerals present these mothers as new examples of self-sacrifice and martyrdom. This book re-centers the history of the Renaissance around women and their bodies - both as subjects of artistic representation and as critical but ignored contributors to Florentine society. It proposes a more inclusive vision of an era that is still too often addressed exclusively via the history of its male artists, bankers and merchants. Women, Fertility and Maternal Art in Renaissance Florence appeals to both students and scholars in field of Art History, Renaissance Art and Gender Studies, but is also suitable for the general reader with interest in these areas"--